Dimensions of cultural sustainability—Local adaptation, adaptive capacity and social resilience - Järvelä, Marja (Frontiers in Political Science, 2023)
Cultural sustainability relates to sustainable development. According to UNESCO “culture provides the necessary transformative dimension that ensures the sustainability of development processes.” Originally sustainable development was defined through three dimensions-ecological, economic and social dimension. Further, the social dimension has been understood in multiple ways often accentuating socio-economic assets of development rather than socio-cultural capacities. Eventually, there has been an increasing interest in defining cultural sustainability as a fourth pillar of sustainable development. While becoming aware of the contemporary supranational risks such as climate change, COVID 19-pandemia or escalating military conflicts, sustainable development can hardly be envisioned in terms of linear progress but rather considered with anticipation of eventual shocks, interruptions, and vulnerabilities related to development. In this perspective, cultural sustainability can be increasingly associated with identifying vulnerabilities and with envisioning attainable measures of adaptation. This article addresses the complex issue of defining cultural sustainability through lenses of social resilience and adaptive capacity at local level.